Rate of decline in residual kidney function and cognitive impairment in incident haemodialysis patients: A prospective, longitudinal analysis of the BISTRO trial cohort - Kerry-Lee Rosenberg; Indranil Dasgupta; Dorothea Nitsch; John Belcher; Ken Farrington; Simon Davies (PLoS ONE, 2026)
Background Previous studies suggest loss of residual kidney function (RKF) on haemodialysis is associated with cognitive impairment (CI). This study investigated the association of rate of change in RKF with risk of new CI and change in cognition after haemodialysis initiation and the association between dialysis treatment parameters and changes in cognition. Methods This prospective cohort study used data from the Bioimpedance Spectroscopy to Maintain Renal Output trial (BISTRO). Cognition was assessed using the Montreal Cognitive Assessment (MoCA). Logistic regression and generalised estimating equations were used to estimate the association of rate of decline in RKF and clinical parameters with risk of CI at 12 and 24 months after haemodialysis start and mean change in MoCA score per year. Results The study included 435 participants. Rate of decline in RKF was not associated with risk of CI at 12 or 24 months or with mean change in MoCA score. Higher dialysate temperature was associated with a mean annual improvement in MoCA score of 1.12 per one degree Celsius (95% CI 0.23 to 2.01). Amongst those without left ventricular failure, an interdialytic weight gain ≥2 kg was associated with an annual increase in MoCA score of 1.62 (95% CI 0.21 to 3.04), compared to those with weight gains ≤0.5 kg. Conversely, a weight gain ≥2 kg was associated with a worsening MoCA score of −3.08 (95% CI −5.76 to −0.40) amongst those with left ventricular failure (p-value for interaction < 0.001). Conclusions We found no association between rate of decline in RKF and cognitive performance. These findings may reflect selection bias or the effect of relatively slow rate of decline in RKF. Higher interdialytic weight gains were associated with worsening cognition amongst those with left ventricular failure, underscoring another challenge of fluid management in this group of patients.